Yeast hydrolysate and exercise ameliorate high-fat diet-induced obesity in C57BL/6 mice - Nari Kim; Yejin Ahn; Eun-Jin Jung; Hyeon-Son Choi; Hyung Joo Suh; Yeok Boo Chang (BMC Complementary Medicine and Therapies)
Abstract Background Yeast hydrolysate (YH) has been shown to be effective in inhibiting fat accumulation. This study aimed to investigate the effects of YH and exercise on high-fat diet-induced obesity and their underlying mechanisms in C57BL/6J mice. Methods In this study, 6-week-old C57BL/6 mice were divided into 7 groups; a normal group fed a normal chow diet, an HFD group (CON) fed ad libitum, an exercise group (15m/min, 30min), an HFD supplemented with low dose of YH (100 mg/kg, YHL), an HFD supplemented with high dose of YH (200 mg/kg, YHH), and a combination of exercise and YHH group. After 12 weeks of HFD and YH administration, white adipocytes and liver tissue were analyzed. Results Both YH and exercise significantly reduced the weight of the body and adipose tissues; however, the greatest effect was observed when YH and exercise were combined. Similarly, most reduction in adipocyte size and fat formation in the liver was notable following the combination of YH and exercise. Furthermore, both YH and exercise effectively downregulated lipid synthesis genes, namely fatty acid synthase (FAS), acetyl-CoA carboxylase (ACC), and HMG-CoA reductase (HMGCR), and SREBP1 and SREBP2 proteins. YH and/or exercise also significantly increased the mRNA levels of hormone sensitive lipase (HSL) and carnitine palmitoyltransferase 1 (CPT1), both of which are related to fatty acid oxidation. In addition, pAMPKα and PPARα levels were significantly increased by YH and exercise, with the greatest increase noted following the combination of YH and exercise. Additionally, YH and exercise combined caused the most significant increase in the antioxidant response, as evidenced by nuclear factor erythroid 2-related factor 2 (Nrf2) and superoxide dismutase 1 (SOD1) upregulation at protein and mRNA levels. Their combination also exhibited strongest suppression of inflammatory responses via the downregulation of NF-κB, TNF-α, and IL-1β at protein and mRNA levels. Collectively, YH and exercise combination showed an inhibitory effect on obesity, leading to decreased lipogenesis and increased lipolysis, with favorable regulation of antioxidant and inflammatory responses. Conclusion This study suggests the potential use of a combination of physical activity and YH supplementation to control obesity and related metabolic diseases.